Studying Abroad at Chonnam National University during the COVID-19 Pandemic (Comparative & International Education Series, 2022)
The first time I was able to do a study abroad program was in 2016, which I ended up doing at Purdue University Northwest (PNW) in the USA. Being that I am from Germany, it had been a dream of mine to live in the USA for a while and experience what I had only been able to see from afar in movies, TV shows, and books. My plan was always to go to the USA for one semester and scratch the itch that I had for years at that point. But things turned out differently than what I had originally thought. Instead of satisfying my need, that itch only grew stronger while in the USA, and every day after I returned home to Germany. I started to volunteer at my school’s international office, held presentations for fellow students about why they should study abroad, and already planned how I could go abroad again, but this time for longer. The idea was to go back to PNW as a self-funded degree-seeking student and work towards earning a master’s degree, working as a teacher assistant (TA) for fee remission and also at the international office to support any costs that would arise. When the time for my bachelor’s thesis came in Germany, I unexpectedly got an offer to write it at Michigan State University as an exchange research assistant for one semester with all expenses covered. While I was back in the USA, I finalized all the things that needed to be done to return for my graduate degree at PNW.